Front Cover: A Quadrupolar Bis‐Triarylborane Chromophore as a Fluorimetric and Chirooptic Probe for Simultaneous and Selective Sensing of DNA, RNA and Proteins (Chem. Eur. J. 10/2020). Issue 10 (24th January 2020) - Ban, Željka; Griesbeck, Stefanie; Tomić, Sanja; Nitsch, Jörn; Marder, Todd B.; Piantanida, Ivo
Abstract : One dye to detect them all : A tetracationic quadrupolar bis‐triarylborane dye can bind with 10–100 nM affinity and efficiently distinguish between DNA/RNA and BSA by characteristic fluorescence emission points separated by Δ ν ˜ =3600 cm −1, allowing the simultaneous quantification of DNA/RNA and protein (BSA) in a mixture. The applicability of such fluorimetric differentiation in vitro was demonstrated, strongly supporting a protein‐like target as a dominant binding site of this dye in human cells. More information can be found in the Full Paper by T. B. Marder, I. Piantanida, et al. on page 2195 .